To Study the Cardiac Autonomic Functions in Leprosy Patients, a Hospital Based Study- an Original Research Article - Dr. Usha Kataria (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Aims and Objectives The aim of this study was to evaluate cardiac autonomic functions in leprosy patients and to compare the same between paucibacillary, multibacillary leprosy patients and with the normal healthy subjects. Materials and Methods We studied twenty five paucibacillary, twenty five multibacillary leprosy patients and twenty five age matched healthy subjects. Non invasive bedside tests i.e. orthostatic test, Valsalva ratio, hand grip test, effect of deep breathing and standing were studied in all subjects. Results Both sympathetic and parasympathetic functions were altered in both the leprosy groups when compared to normal subjects. On intergroup comparison we observed that the paucibacillary group had higher values then the multibacillary leprosy group. Conclusion To comment regarding the alteration in cardiac autonomic function, this was a very small study group, we need larger study group to reach the proper conclusion.